Nominal arguments and language variation - Jiang, Li Julie (Oxford University Press, 2021)
"This book investigates nominal arguments in classifier languages. A long-held claim is that classifier languages do not have overt article determiners (D). This book, however, brings to the forefront of the theoretical investigation on the typologically unique Nuosu Yi, a classifier language that will be shown to have an overt article determiner. By comparing nominal arguments in Nuosu Yi to those in Mandarin, the book provides a parametric account of variation among classifier languages and extends the account to argument formation in general. This book begins with a detailed examination of bare numeral classifier phrases in Mandarin by comparing them with bare numeral noun phrases in number marking languages, such as English, French, and Russian. Lastly, the book puts the analysis of Mandarin and Nuosu Yi nominal arguments in a broader, cross-linguistic perspective and develops a parametric account of variation in nominal argument formation in general"--
Keywords: Numerativ; Nosu-Sprache; Artikel -- Linguistik; Chinesisch; Nominalphrase; Classifiers (Linguistics); Yi language / Classifiers; Yi language / Syntax; Chinese language / Classifiers; Chinese language / Syntax; Hochschulschrift